2017
DOI: 10.4103/2152-7806.198735
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of porous custom-made hydroxyapatite implants 6 months and 2.5 years after cranioplasty

Abstract: Background:In cranial reconstruction, the features of artificial bone differ. Custom-made porous hydroxyapatite (HAp) implants for cranioplasty have been used all over the world because of their good cosmetic, biocompatibility, and osteoconductive properties. Surgical techniques were analyzed, and histological assessment of new bone formation in the hydroxyapatite was performed.Methods:Over a 6-year time period, 41 patients underwent cranioplasty using a custom-made three-dimensional hybrid pore structured hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Hydroxyapatite-based biomaterials possess osteoconductive properties and can also act as three-dimensional scaffolds to support bone regeneration [1]. However, introducing biomaterials into the body can lead to metabolic alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite-based biomaterials possess osteoconductive properties and can also act as three-dimensional scaffolds to support bone regeneration [1]. However, introducing biomaterials into the body can lead to metabolic alterations.…”
Section: Introductionmentioning
confidence: 99%
“…In 95% percent of cases, it is accompanied by hydrocephalus and myelomeningocele. Types 3 and 4 are rare [ 1 , 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy itself, uterine contractions and maternal effort during vaginal delivery could increase intracranial pressure, aggravate maternal symptoms and worsen the condition. Anesthesia for labor analgesia or obstetric surgery is a matter of debate as general, epidural or spinal anesthesia can all have consequences [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hydroxyapatite porous ceramic have a chemical composition that stimulates osteoblast colonization and osteointegration in up to 83.3% of cases [5] . Ono et al [6] showed the new bone formation in vivo after cranioplasty. Furthermore, a ceramic implant may be successfully used to cover a large skull defect after bone removal in a single-step reconstructive procedure under image guidance [7] , and the feasibility of cranioplasty using hydroxyapatite ceramic has already been reported in pediatric patients [5,8,9] .…”
Section: Discussionmentioning
confidence: 99%